"I Wouldn't Change Who I've Become": Released Juvenile Lifers on Joy, Shame, and the Journey to an Integrated Self. (February 2023) - Abrams, Laura S.; Canlione, Kaylyn C.; Washington, Durrell M.
Using phenomenological methodology, the authors explore the core emotions involved in the transition from imprisonment to society for released juvenile lifers and how these emotions inform participants' sense of self. Nine adult men, who had spent an average of 26 years imprisoned for homicide crimes committed as youth, participated in a series of in-depth interviews following their resentencing and release. Using interpretative phenomenological analysis, we found that reintegration following a life sentence involves powerful emotions of joy and shame, and that these emotions can be reconciled to achieve an integrated sense of self—one that embodies self-acceptance and positive self-regard. The findings add to prior theory and research and offer new understandings of the reintegration process for released juvenile lifers.